2017
DOI: 10.3389/fpls.2017.00975
|View full text |Cite
|
Sign up to set email alerts
|

MATI, a Novel Protein Involved in the Regulation of Herbivore-Associated Signaling Pathways

Abstract: The defense response of the plants against herbivores relies on a complex network of interconnected signaling pathways. In this work, we characterized a new key player in the response of Arabidopsis against the two-spotted spider mite Tetranychus urticae, the MATI (Mite Attack Triggered Immunity) gene. This gene was differentially induced in resistant Bla-2 strain relative to susceptible Kon Arabidopsis accessions after mite attack, suggesting a potential role in the control of spider mites. To study the MATI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 103 publications
(155 reference statements)
3
45
0
Order By: Relevance
“…It has also been reported that the effect of the mite attack triggered immunity (MATI) gene involved in the maintenance of the thale cress antioxidant status was correlated with the spider mite performance. MATI-overexpressing plants led to a moderate H 2 O 2 accumulation and increased thale cress resistance to spider mite attack as reflected by lesser leaf damage and the reduced mite fecundity observed in comparison to the symptoms and oviposition rates quantified in control and mutant plants [70].…”
Section: Inducible Defenses: Early Signalling Eventsmentioning
confidence: 86%
See 2 more Smart Citations
“…It has also been reported that the effect of the mite attack triggered immunity (MATI) gene involved in the maintenance of the thale cress antioxidant status was correlated with the spider mite performance. MATI-overexpressing plants led to a moderate H 2 O 2 accumulation and increased thale cress resistance to spider mite attack as reflected by lesser leaf damage and the reduced mite fecundity observed in comparison to the symptoms and oviposition rates quantified in control and mutant plants [70].…”
Section: Inducible Defenses: Early Signalling Eventsmentioning
confidence: 86%
“…However, not only the JA pathway is activated after spider mite infestation. The induction of both JA and SA pathways has been reported in spider mite infested thale cress [42,64,70], tomato [44,47], citrus [40,43,80] and pepper [46], among other plant species. Moreover, He et al [81] also reported the accumulation of SA and conjugated-SA forms induced by spider mite attack in bean (Phaseolus vulgaris) leaves but the JA content was not analyzed in this study.…”
Section: Inducible Defenses: Early Signalling Eventsmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, the relevance of IGs in defence was assessed using IG mutant lines on which the development of T. urticae was increased. A microarray analysis of spider mites reared on IG mutants or wild-type plants showed that the increased expression of detoxification genes such as P450 monooxygenases, glycosyltransferases, and lipocalins correlated with IG levels [ 89 , 105 ]. Note that the implication of glucosinolates was demonstrated using lines grown on Phaseolus vulgaris .…”
Section: Plant Defence Mechanisms That Contribute To a Sustainablementioning
confidence: 99%
“…The retarded induction of HvPap-1 after spider mite infestation could be more related to senescence processes associated to leaf damage. This hypothesis is supported by the fact that jasmonic acid not only triggers defensive responses against herbivores but also leaf senescence ( Reinbothe et al, 2009 ), and the reported induction of the jasmonic acid biosynthesis and signaling pathways after spider mite feeding ( Ament et al, 2004 ; Martel et al, 2015 ; Santamaria et al, 2017 ). Therefore, if the induction of HvPap-1 is due to different mechanisms, the analysis of the transcriptome in silencing or overexpressing HvPap-1 lines could help to understand the differential responses to pathogen and herbivore stresses.…”
Section: Discussionmentioning
confidence: 86%